2016
DOI: 10.1002/acr.22861
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of Fatigue Following Total Knee Replacement: A Longitudinal Cohort Study

Abstract: Among patients undergoing TKR for OA, clinically important fatigue is considerably prevalent both before and for at least 6 months after surgery. Identifying and addressing early predictors of ongoing fatigue has the potential to improve the quality of life following TKR surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 29 publications
2
21
0
Order By: Relevance
“…The results of this study were in line with those of Murphy et al’s () study, which found that the association between pain severity and physical function differs throughout the day, indicating that physical function is a mediating variable between pain and quality of life. Nevertheless, the relationship between pain and fatigue was in accordance with other studies, in which knee pain was associated with fatigue (Hodges et al, ; Murphy et al, ). Fatigue is a common feature of chronic conditions (Engberg, Segerstedt, Waller, Wennberg, & Eliasson, ; MacKean, Stewart, & Maddocks, ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of this study were in line with those of Murphy et al’s () study, which found that the association between pain severity and physical function differs throughout the day, indicating that physical function is a mediating variable between pain and quality of life. Nevertheless, the relationship between pain and fatigue was in accordance with other studies, in which knee pain was associated with fatigue (Hodges et al, ; Murphy et al, ). Fatigue is a common feature of chronic conditions (Engberg, Segerstedt, Waller, Wennberg, & Eliasson, ; MacKean, Stewart, & Maddocks, ).…”
Section: Discussionsupporting
confidence: 91%
“…Progressive physical limitations and disability lead to diminished quality of life (Mesci, Icagasioglu, Mesci, & Turgut, ). Pain subsequent to knee OA also impacts well‐being through incremental fatigue (Hodges et al, ), distress, and depressive symptoms, again affecting quality of life (Sugai et al, ). The symptom cluster of pain, fatigue, and depressive symptoms is related to functional status and quality of life among older people with knee OA (Jenkins & McCoy, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A “0” on the fatigue VAS was defined as “no fatigue” and “10” was defined as “fatigue as bad as it can be” with higher values indicating greater fatigue severity. The VAS fatigue scale has been commonly used in OA research and it is also a valid, reliable and responsive tool for subjective measurement such as fatigue . Further, in rheumatic diseases, VAS fatigue strongly correlates with other fatigue measures such as the Multidimensional Assessment of Fatigue at 0.80, Short‐Form 36 vitality subscale (SF‐36 VT) at 0.71 and the Multidimensional Fatigue Inventory (MFI)‐total and MFI‐general fatigue at 0.62‐0.70 …”
Section: Methodsmentioning
confidence: 99%
“…Fatigue is a commonly reported symptom and a major contributor to substantial disability and decreased quality of life among individuals with knee osteoarthritis (OA) . Generalized fatigue affects almost half of adults with OA and its prevalence has been reported to be as high as 40% . Individuals with OA describe fatigue as a symptom that considerably impacts daily functioning, social life and all aspect of daily living .…”
Section: Introductionmentioning
confidence: 99%